The trajectory of sanitary regulation for the use of the lactase enzyme in food products in Brazil (Research, Society and Development, 2021)
Objective: Analyze the trajectory of sanitary regulation of lactase in food products in Brazil. Methodology: This is an exploratory-descriptive, qualitative research, carried out from the analysis of sanitary regulations and secondary public access data on food records and patents. Results: It was observed that the 24 normative acts presented weaknesses and inconsistencies that allowed the transition from the use of lactase as a supporting element in food technology, to deliberate use in food products registered in different categories. Among these categories, foods with functional property or health claims and food supplements containing probiotics and/or enzymes predominated. In addition, it was verified the patent registration of the medicine by the manufacturer, orodispersible tablet containing lactase as active principle, and subsequent registration of the food product with Anvisa, containing the enzyme, with functional/health claim. Conclusion: In short, the findings evidenced the redirection of the use of lactase from the pharmaceutical market to the potential food market, as well as failures in guidance for consumer safety, for which conflicts of interest and precedents for its indiscriminate marketing are recognized.